Mycoparasitic potential of growth promoting Trichoderma strains against phytopathogens - Dwivedi, Meenakshi; Tewari, Anand Kumar (Annals of Agricultural Research, 2018)
Six isolates of Trichoderma asperellum viz. TRS W4, TRP W8, TRS R4, TRS R8, TRP C3 and TRP C4obtained from rhizosphere and rhizoplane of wheat, rice and chickpea were selected for their growthpromoting efficacy in their native crops. These 06 isolates were tested for their biological controlpotential against plant pathogens viz., Rhizoctonia solani (isolates from rice and chickpea), Sclerotiniasclerotiorum (isolate from chickpea) and Bipolaris sorokiniana (isolate from wheat) under in vitroconditions. Dual culture studyrevealed that all the Trichoderma isolates along with Th-14, commercialTrichoderma harzianum strain used as positive control, completely parasitized, i.e. 100% mycelialparasitiation, the growth of all test plant pathogens.